A new species of Acherontides (Collembola: Hypogastruridae) from Brazil, with an identification key - de Lima, Estevam C. Araujo; Stievano, Luis Carlos; Zeppelini1, Douglas (Zootaxa, 2019)
A second species of Acherontides from Brazil is described. Acherontides serrasapoensis sp. nov. has two ocular area chaetae, tenaculum with 3+3, two clavate tenent hairs, and anal spines about 1/3 the length of unguis III. A comparative table is presented and an identification key for the species of Acherontides.